An efficient amplification strategy for N-doped NiCo2O4 with oxygen vacancies and partial Ni/Co-nitrides as a dual-function electrode for both supercapatteries and hydrogen electrocatalysis. Issue 4 (28th November 2018) - Choi, Keorock; Moon, In Kyu; Oh, Jungwoo
Abstract : N-doped NCO electrodes exhibited excellent electrochemical performance for supercapacitors and hydrogen evolution reaction electrocatalysis in KOH electrolyte. Abstract : To obtain transition-metal-oxide-based materials with remarkable energy storage and conversion performance, rational design and synthesis of electrodes with abundant active sites is crucial. Herein, we propose an effective strategy for nitrogen doping in NiCo2 O4 (NCO) nanowire arrays using NH3 plasma treatment. N-doped NCO contains oxygen vacancies with nitrogen atoms, nickel/cobalt nitrides, and high concentrations of Ni 2+ and Co 2+ within the structure, leading to high electrical conductivity. As expected, N-doped NCO electrodes exhibited excellent electrochemical performance for supercapacitors and hydrogen evolution reaction (HER) electrocatalysis in KOH electrolyte. This work provides a promising pathway toward developing advanced electrodes.